High-concentration inorganic nanoparticle polyester master batch and preparation method thereof

The high-concentration inorganic nanoparticle polyester masterbatches were synthesized through chemical methods, and alkaline earth metal acid salt compounds were used to adjust the acid-base and control the addition method, which solved the problem of inorganic particle agglomeration, achieved high dispersion and high content, reduced spinning costs and improved production efficiency.

CN119505490APending Publication Date: 2025-02-25TORAY FIBER RES INST(CHINA) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311086582.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to prepare high-concentration inorganic nanoparticle polyester masterbatches, resulting in agglomeration of inorganic particles, clogging of spinning prefilters and reduced service life of spinning components.

Method used

High-concentration inorganic nanoparticle polyester masterbatches were synthesized by chemical methods, and the acidity and alkalinity of the polymerization system was adjusted by alkaline earth metal acid salt compounds, inhibit the agglomeration of inorganic nanoparticles, and optimize the dispersion effect of inorganic nanoparticles by controlling the addition speed and timing of addition.

Benefits of technology

The high dispersion and high content of inorganic nanoparticles in polyester masterbatches are achieved, which reduces spinning costs, extends the service life of spinning modules, and improves the efficiency of spinning production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-concentration inorganic nanoparticle polyester master batch and a preparation method thereof. The polyester master batch is mainly composed of polyester and inorganic nanoparticles, and the inorganic nanoparticles are added before condensation polymerization. The content of the inorganic nano particles is 15 to 60 weight percent; the polyester master batch contains 15 to 130 ppm of alkaline earth metal elements; the molar ratio of the alkaline earth metal element to the carboxyl at the terminal of the polyester is (0.008-0.070): 1. The polyester master batch disclosed by the invention is low in preparation cost, high in inorganic particle content, uniform in dispersion, good in filterability in a subsequent spinning process, slow in spinning filter pressure rise and free from blocking a spinning assembly, the service life of the spinning assembly is prolonged, the spinning cost is reduced, and meanwhile, the spinning production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an inorganic nanoparticle polyester masterbatch, in particular to a polyester masterbatch with high inorganic nanoparticle content and good dispersibility. Background Art

[0002] Polyester fiber was invented in the 1940s. In the 1970s, with the development of the chemical industry, it gradually surpassed nylon and became the king of chemical fibers. With the continuous improvement of people's living standards, the requirements for clothing have also gradually changed dramatically. From the pursuit of semi-matte clothing that eliminates gloss, to the high-gloss and super-gloss clothing with good gloss, it has developed into matte clothing with good matte soft effect, deep dyeability and excellent light resistance, and then developed into full-matte high-end fabrics with excellent light-shielding properties and elegant gloss similar to pure cotton. This shows that consumers' aesthetic concepts are constantly sublimating and changing with the change of time. Therefore, chemical fiber manufacturers are eager to realize the adjustable matte property of polyester fiber, so as to face consumers' aesthetics that keep pace with the times with high efficiency and low cost. To achieve this demand, there are usually two ways. One is the modification method, that is, modifying the existing fiber in the post-processing of the fabric, so that its surface refractive index changes, and the light is diffusely reflected in different directions, so as to achieve the ideal matte visual effect. However, this method has high post-processing costs, and the matte effect is uncontrollable, and the product is uncontrollable in industrial large-scale production. The other is the masterbatch method, which adds different types and concentrations of matting agent polymer masterbatches during the spinning process, so that the fiber contains a matting agent with a refractive index different from that of polyester, thereby achieving a controllable gloss effect. This method has high chemical stability, does not change at high temperatures, does not disappear during post-processing and washing, and has a long wearing life. Therefore, the development of polyester masterbatches is particularly important.

[0003] With the development of the polyester masterbatch industry, the development trend of masterbatch is gradually tending towards high concentration, which puts forward higher requirements for the dispersion of inorganic particles in polyester. Japanese Patent Laid-Open No. 3-287655 proposes to use mixing and extruding technology to mix high-concentration inorganic particles with polyester, but the mixing process undoubtedly increases the production cost, and the inorganic particles in the polyester masterbatch obtained by this method have a high probability of agglomeration, which will produce a large number of 5-10μm coarse particles, causing the clogging of the spinning pre-filter and the reduction of the service life of the spinning component in the subsequent spinning process. Japanese Patent Laid-Open No. 2002-356547 and Laid-Open No. 2006-265376 mention the use of chemical polymerization methods to synthesize high-concentration inorganic particle masterbatches, but the highest content of inorganic particles they disclose is only 10wt%, which cannot prepare high-concentration inorganic particle dispersion masterbatches and achieve the application effect of super matting. Summary of the invention

[0004] The object of the present invention is to provide a polyester masterbatch which is synthesized by a chemical method and has a high content of inorganic nanoparticles and good dispersibility.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is: The high-concentration inorganic nanoparticle polyester masterbatch is mainly composed of polyester and inorganic nanoparticles. The content of the inorganic nanoparticles is 15-60wt%; the polyester masterbatch contains 15-130ppm of alkaline earth metal elements; the molar ratio of the alkaline earth metal elements to the polyester terminal carboxyl group is 0.008-0.070:1.

[0006] The molar ratio of the inorganic nanoparticles to the alkaline earth metal element is preferably 600-4000:1.

[0007] The inorganic nanoparticles are preferably at least one of titanium dioxide, silicon dioxide, zirconium oxide, zinc oxide, and barium sulfate.

[0008] The average particle size of the inorganic nanoparticles is preferably less than 1000 nm, and the variance value of the particle size of the inorganic nanoparticles is preferably less than 500.

[0009] The alkaline earth metal element is preferably calcium ion and / or magnesium ion.

[0010] The polyester masterbatch is heated at a temperature of 290°C and a shear rate of 121.6s -1 The melt viscosity is preferably 2500 Pa·s or less.

[0011] The present invention also discloses a method for preparing the above-mentioned high-concentration inorganic nanoparticle polyester masterbatch, which mainly comprises the following steps: subjecting terephthalic acid or its esterified derivative and diol to an ester exchange or esterification reaction under the action of a catalyst, and then subjecting the terephthalic acid to a polycondensation reaction; adding an alkaline earth metal acid radical salt compound equivalent to 15 to 130 ppm of the polyester masterbatch in terms of alkaline earth metal elements during the ester exchange or esterification reaction; and adding inorganic nanoparticles equivalent to 15 to 60 wt % of the polyester masterbatch at a rate of 0.10 to 1.20 wt % / min before the start of the polycondensation reaction.

[0012] The inorganic nanoparticles are preferably added in two times, with the interval between the end of the first addition and the start of the second addition being 20 to 60 minutes.

[0013] The acid ion in the alkaline earth metal acid salt compound is preferably at least one of acetate, butyrate and hydrochloride, and the alkaline earth metal ion is preferably calcium and / or magnesium.

[0014] The polyester masterbatch of the present invention has low preparation cost, high content of inorganic particles, uniform dispersion, good filterability in the subsequent spinning process, slow increase in spinning filter pressure, no clogging of the spinning assembly, extended the service life of the spinning assembly, reduced spinning costs and simultaneously improved the efficiency of spinning production. DETAILED DESCRIPTION

[0015] Since inorganic nanoparticles have large specific surface area and high specific surface energy, they tend to agglomerate in a matrix with a polymer such as polyester as a dispersion medium. The present invention prepares a polyester masterbatch with high concentration of inorganic nanoparticles by designing a chemical synthesis method. Through a filter pressure test, it is confirmed that the dispersibility of inorganic nanoparticles in the polyester masterbatch is better than that of commercially available inorganic nanoparticle masterbatch prepared by mixing and extrusion.

[0016] The content of inorganic nanoparticles in the polyester masterbatch is 15 to 60wt% relative to the weight of the polyester masterbatch. If the content of inorganic nanoparticles in the polyester masterbatch is greater than 60wt%, the fluidity of the polyester polymerization system will deteriorate, adhesion will occur in the reactor, and the product rate of the polyester masterbatch will be reduced; at the same time, during the melt spinning process, high-density inorganic nanoparticles are prone to agglomeration in the polyester substrate, resulting in an increase in the filter pressure during the spinning process and an increase in the spinning cost. If the content of inorganic nanoparticles in the polyester masterbatch is less than 15wt%, according to cost calculation, the economic value of the polyester masterbatch as a spinning masterbatch is not high, but it will lead to an increase in production costs.

[0017] Whether the inorganic nanoparticles in the polymerization system agglomerate or not depends on the size of their zeta potential (electromotive potential). When the absolute value of the zeta potential of the inorganic nanoparticles is below 30mV, they are in the agglomeration field, and the inorganic nanoparticles are more likely to agglomerate, which will cause the inorganic particles in the obtained polyester masterbatch to be too large in size. When used for subsequent fiber preparation, the spinning filter pressure rises seriously, and the spinning assembly needs to be replaced frequently, which not only affects productivity but also increases the spinning cost; when the absolute value of the zeta potential of the inorganic nanoparticles is greater than 30mV, they are in the dispersion field, and the inorganic nanoparticles are not easy to agglomerate. The presence of carboxyl groups in the polymerization system changes the pH environment of the inorganic nanoparticles when they are in the stable zeta potential field, causing the zeta potential to shift to the agglomeration field. In order to prevent the shift of the zeta potential of the inorganic nanoparticles, the present invention is mainly achieved by adding alkaline earth metal acid salt compounds during the polyester reaction process. The alkaline earth metal acid salt compound is alkaline and can balance the acidic polyester reaction system, so that the pH value of the system is far away from the isoelectric point of the inorganic nanoparticles, that is, the zeta potential of the inorganic nanoparticles is always controlled to be below -30mv, thereby inhibiting the agglomeration of the inorganic nanoparticles. When the content of the alkaline earth metal element in the polyester masterbatch is lower than 15ppm relative to the polyester masterbatch, it is not enough to reach the level of adjusting the pH of the system, so it is impossible to produce an effective inorganic nanoparticle agglomeration inhibition effect. When the content of the alkaline earth metal element in the polyester masterbatch is higher than 130ppm relative to the polyester masterbatch, too much alkali metal ions will destroy the relatively stable double layer of the inorganic nanoparticles. Specifically, the alkaline earth metal ions are attracted by the negative charge on the surface of the inorganic nanoparticles and enter the sliding surface of the inorganic nanoparticles, resulting in a decrease in the charge of the inorganic nanoparticles, and the zeta potential approaches the 0mV direction, entering the agglomeration field, resulting in thermodynamic instability of the particles, thereby inducing the agglomeration of the inorganic nanoparticles, causing the phenomenon of floating and broken silk in the subsequent spinning process, affecting the spinning stability and increasing the production cost.

[0018] As described above, the alkaline earth metal acid salt compound achieves the purpose of dispersing inorganic nanoparticles by adjusting the acidity and alkalinity of the polymerization system. The acidity of the polymerization system mainly comes from the terminal carboxyl content therein. Since the terminal carboxyl shows acidity, the more the terminal carboxyl content, the smaller the pH value of the polymerization system. The present invention characterizes the degree of adjustment of the acidity and alkalinity of the polymerization system by the alkaline earth metal acid salt compound through the molar ratio of the alkaline earth metal element to the terminal carboxyl content of the polyester in the polyester masterbatch. The inventor of the present invention has found that when the molar ratio of the alkaline earth metal element to the terminal carboxyl of the polyester is in the range of 0.008 to 0.070:1, the acid-base environment of the polymerization system represented can effectively inhibit the agglomeration of inorganic nanoparticles. When the molar ratio of the alkaline earth metal element to the terminal carboxyl group of the polyester is lower than 0.008:1, the alkaline earth metal acid radical compound added during the polymerization process is insufficient to change the influence of the terminal carboxyl group on the pH value of the polymerization system. As the polymerization reaction proceeds, the terminal carboxyl content of the polyester increases, and the pH of the polymerization system moves toward the acidic direction, deviating from the pH value of the zeta potential when the inorganic nanoparticles are in a stable state. The inorganic nanoparticles are prone to agglomeration, and the spinning filter pressure increases during subsequent use, requiring more frequent replacement of the spinning assembly, which affects both productivity and increases spinning costs. When the molar ratio of the alkaline earth metal element to the terminal carboxyl group of the polyester is greater than 0.070:1, excessive alkali metal ions will destroy the relatively stable double layer of the inorganic nanoparticles, resulting in thermodynamic instability of the particles, triggering agglomeration of the inorganic nanoparticles, causing floating and broken silk in the subsequent spinning process, affecting spinning stability and increasing production costs. In order to obtain a better dispersion effect of the inorganic nanoparticles in the polyester masterbatch, the molar ratio of the alkaline earth metal element to the polyester terminal carboxyl group is preferably 0.010 to 0.050:1.

[0019] In addition to adjusting the acid-base environment of the polymerization system, based on the principle of opposite charges attracting each other, when the molar ratio of alkaline earth metal elements to inorganic nanoparticles is appropriate, the alkaline earth metal elements can also form a coating layer of a certain thickness outside the sliding surface of the inorganic nanoparticles to prevent the agglomeration of the inorganic nanoparticles. When the molar ratio of the inorganic nanoparticles to the alkaline earth metal elements in the polyester masterbatch is too high, the alkaline earth metal ions cannot form a coating layer on the surface of the inorganic nanoparticles and cannot inhibit the agglomeration of the inorganic nanoparticles; when the molar ratio of the inorganic nanoparticles to the alkaline earth metal elements in the polyester masterbatch is too low, the excess alkaline earth metal ions will destroy the double electrical layer of the inorganic nanoparticles and enter the sliding surface of the inorganic nanoparticles, resulting in instability of the inorganic nanoparticles, and agglomeration will also occur, affecting the subsequent spinning process. Therefore, the molar ratio of the inorganic nanoparticles to the alkaline earth metal elements in the present invention is preferably 600 to 4000:1, and more preferably 1500 to 3000:1.

[0020] The present invention does not particularly limit the type of the inorganic nanoparticles, as long as they can impart anti-penetration properties to the fiber textile. Considering the anti-penetration properties and the dispersibility in polyester, the present invention preferably uses at least one of titanium dioxide, silicon dioxide, zirconium oxide, zinc oxide, and barium sulfate, and more preferably titanium dioxide. The inorganic nanoparticles can be used alone or in combination of two or more. However, when inorganic nanoparticles are mixed, there is the influence of mutual interference of potentials between particles of different types and the offset of zeta potential, which may increase the risk of agglomeration, so careful selection is required when mixing.

[0021] As is known to all, if there are large particles in the system during polymerization, it will lead to large polymerization stirring resistance and the reaction will not be easy to proceed. At the same time, during spinning, if there are large particles in the melt, it is easy to clog the filter screen in the spinning assembly, causing the assembly pressure to rise rapidly, exceeding the upper limit of the pressure that the assembly can use in a short time, and the machine must be shut down, affecting productivity; and the number of broken and floating filaments increases during the spinning process, affecting the spinning production operability and the basic physical properties of the fiber. After the dispersibility of inorganic nanoparticles in polyester masterbatch is improved by adding alkaline earth metal acid salt compounds, the particle size of the inorganic nanoparticles of the present invention is small and will not have an adverse effect on the subsequent spinning process. By adjusting a series of values ​​such as the amount of alkaline earth metal acid salt compounds added (i.e., the content of alkaline earth metal elements in polyester masterbatch), the molar ratio of alkaline earth metal elements to polyester terminal carboxyl groups, and the content of inorganic nanoparticles, the average particle size of the inorganic nanoparticles in the polyester masterbatch of the present invention is preferably less than 1000nm, more preferably less than 500nm. At the same time, the variance value of the particle size of the inorganic nanoparticles is preferably less than 500, more preferably less than 200. The variance value of the particle size can characterize the difference in the particle size of each inorganic nanoparticle in the polyester masterbatch. The smaller the variance value, the more concentrated the particle size of each inorganic nanoparticle is and the more uniform the dispersion is.

[0022] The inherent viscosity IV of the polyester masterbatch obtained in the present invention is preferably within the range of 0.400 to 0.600 dL / g. The inherent viscosity IV of the polyester masterbatch affects both the preparation process of the polyester masterbatch and the spinnability of the masterbatch during the spinning application process. If the inherent viscosity IV of the polyester masterbatch is too low, the phenomenon of broken and floating filaments will occur during the spinning process due to the low molecular weight of the polyester, resulting in the consequence of being unspinnable; if the inherent viscosity IV of the polyester masterbatch is too high, the melt viscosity of the polymerization system in the polymerization reactor is particularly large, the fluidity becomes poor, it is not easy to spit out, the yield of the polyester masterbatch decreases, and the reaction time in the synthesis process of the polyester masterbatch is prolonged, which will cause the color tone of the polyester masterbatch to turn yellow, and in severe cases, the obtained polyester masterbatch will be unusable. Therefore, the inherent viscosity IV of the polyester masterbatch of the present invention is more preferably 0.450 to 0.550 dL / g.

[0023] The melt viscosity of the polyester masterbatch has an impact on the dispersibility of the inorganic nanoparticles. If the melt viscosity of the polyester masterbatch is too high, the dispersibility of the inorganic nanoparticles in the polyester masterbatch is poor, which may easily result in an increase in the filter pressure during the spinning process. Therefore, the polyester masterbatch of the present invention is preferably prepared at a temperature of 290°C and a shear rate of 121.6s -1 The melt viscosity is preferably 2500 Pa·s or less, more preferably between 1000 and 1500 Pa·s.

[0024] The invention also discloses a method for preparing the high-concentration inorganic particle polyester masterbatch, which mainly comprises subjecting terephthalic acid or its esterified derivative and diol to ester exchange or esterification reaction under the action of a catalyst, and then to polycondensation reaction.

[0025] In the transesterification or esterification reaction, an alkaline earth metal acid salt compound is added in an amount equivalent to 15 to 130 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The alkaline earth metal acid salt compound mainly serves as a dispersion stabilizer for inorganic nanoparticles, and can also serve as a catalyst for the transesterification reaction when the main raw materials of the reaction are terephthalate derivatives and diols.

[0026] The reason why the present invention selects alkaline earth metal acid salt compounds instead of alkali metal acid salt compounds with stronger alkalinity is that alkali metal acid salt compounds will destroy the double electric layer of inorganic nanoparticles, reduce the stability of inorganic nanoparticles, and cause the agglomeration of inorganic nanoparticles. The alkalinity of alkaline earth metals is between the alkalinity and neutrality of alkali metals, which is conducive to the zeta potential of inorganic nanoparticles being in a stable position and avoiding the occurrence of agglomeration. The alkaline earth metal element of the present invention is preferably calcium or magnesium. The acid ion in the alkaline earth metal acid salt compound selects short-chain fatty acids, which is conducive to the performance of the alkaline earth metal alkalinity, thereby facilitating the dispersion stability of inorganic nanoparticles in polyester masterbatch. The acid ion can be at least one of acetate, butyrate, caproate, caprylate, caprate, laurate, myristic acid, palmitate, stearate, phosphate, hydrochloride, and sulfate, wherein at least one of acetate, butyrate or hydrochloride is preferred.

[0027] When the amount of the alkaline earth metal acid salt compound added is equivalent to less than 15ppm of the polyester masterbatch in terms of alkaline earth metal elements, the dispersibility of the inorganic nanoparticles cannot be effectively improved, and agglomeration is likely to occur, resulting in poor filtration pressure during the application of the masterbatch and increased spinning costs; at the same time, the catalytic efficiency cannot be guaranteed in the transesterification reaction, and other transesterification catalysts need to be added to enable the transesterification reaction to proceed smoothly, increasing the components. When the amount of the alkaline earth metal acid salt compound added is equivalent to more than 130ppm of the polyester masterbatch in terms of alkaline earth metal elements, excessive alkaline earth metal ions will destroy the double electrical layer of the inorganic nanoparticles, resulting in poor dispersion stability of the inorganic nanoparticles and causing them to agglomerate.

[0028] Another means of improving the dispersibility of inorganic nanoparticles in polyester masterbatch of the present invention is to add inorganic nanoparticles in the polymerization process. By limiting the timing and speed of adding inorganic nanoparticles, the dispersibility of inorganic nanoparticles in the polymerization system can be controlled. First, the inorganic nanoparticles of the present invention are added before the polycondensation reaction. At this time, the viscosity of the polymerization system is relatively small, which is conducive to the dispersion of inorganic nanoparticles. After the polycondensation reaction starts, the melt viscosity of the polymerization system increases, which is not conducive to the dispersion of inorganic nanoparticles. Secondly, regarding the addition speed of inorganic nanoparticles, theoretically, the smaller the addition speed of inorganic nanoparticles, the better the dispersibility in the polymerization system. However, when the addition speed is lower than 0.10wt% / min, the addition time will inevitably be extended under the same total addition amount, and the thermal history time of ester exchange or esterification reaction will be extended, resulting in the deterioration of the color tone of the final polyester masterbatch, affecting its subsequent use. When the addition speed is greater than 1.20wt% / min, the added inorganic nanoparticles are not dispersed in time, and a large amount of accumulation causes the inorganic nanoparticles to agglomerate. Therefore, the addition rate of the inorganic nanoparticles of the present invention is preferably 0.30 to 0.90 wt% / min.

[0029] In addition, the present invention also preferably adds the inorganic nanoparticles twice. When the total amount of inorganic nanoparticles added is constant, adding them twice is beneficial to the dispersion of the inorganic nanoparticles in the polymerization system. Theoretically, the longer the interval between additions, the more beneficial it is for the first added inorganic nanoparticles to disperse in the polyester system. However, if the interval between additions is too long, the thermal history time of the entire ester exchange or esterification reaction is prolonged, resulting in a deterioration in the color tone of the final polyester masterbatch, affecting subsequent use. When the interval between additions is too short, the effect of two additions in promoting the dispersion of inorganic nanoparticles cannot be fully exerted. Considering the performance of the polyester masterbatch and the dispersion effect of the inorganic nanoparticles, the present invention preferably has an interval of 20 to 60 minutes between the end of the first addition and the start of the second addition, and more preferably 20 to 40 minutes.

[0030] The dispersibility of the inorganic nanoparticles in the polyester masterbatch of the present invention can be evaluated by the filter pressure. First, the filter pressure (P1) of 50g of polyester masterbatch is tested at 290°C. The smaller the P1 value, the better the filter pressure of the polyester masterbatch. The P1 of the polyester masterbatch of the present invention is 5.0-20.0MPa. Use bright polyester (without inorganic nanoparticles) to dilute the polyester masterbatch to an inorganic nanoparticle content of 4.5wt%, take 300g to test its filter pressure (P2), the smaller the P2 value, the better the filter pressure of the polyester masterbatch after dilution. The P2 of the polyester masterbatch of the present invention measured after the aforementioned dilution is 0.2-10.0MPa.

[0031] The high-concentration inorganic nanoparticle polyester masterbatch prepared by the chemical polymerization method of the present invention has the price advantages of low preparation cost and high cost performance compared with the polyester masterbatch prepared by mixing and extrusion currently on the market, as well as the performance advantages of good filterability and slow increase in spinning filter pressure during the spinning application process. At the same time, it also extends the service life of the spinning component, improves the efficiency of spinning production, and reduces the spinning cost.

[0032] The physical properties mentioned in the examples were measured by the following methods.

[0033] (1) Terminal carboxyl content (COOH) The optical titration method was used to determine the polyester masterbatch chips. The polyester masterbatch chips were dissolved in a mixture of o-cresol and chloroform (weight ratio 70:30), bromothymol blue indicator was added, and then titrated with 0.05 mol / L potassium hydroxide ethanol solution.

[0034] (2) Determination of alkaline earth metal types and contents The polyester masterbatch is tested by inductively coupled plasma (ICP) technology to obtain characteristic spectral lines. According to the presence or absence of characteristic spectral lines, it is possible to identify whether the sample contains a certain element (qualitative analysis); according to the intensity of the characteristic spectral lines, the content of the corresponding element in the sample is determined (quantitative analysis).

[0035] (3) Polyester masterbatch filtration pressure (P1, P2) Use an ultra-small extruder to perform a filter pressure test. Under certain discharge conditions, the polyester melt is passed through the filter screen with a pore size of 5μm. The filter pressure test temperature is 290℃, and the total discharge of the polyester masterbatch is 50g. The pressure before the filter screen 15 minutes after the start of feeding is recorded as the initial pressure Pa1, and the final pressure at the end of the filter pressure test is recorded as Pa2. At this time, the filter pressure rise value P1 = Pa2-Pa1. The smaller P1 is, the less foreign matter there is in the polyester masterbatch, and the better the dispersibility of the inorganic nanoparticles.

[0036] The polyester masterbatch was mixed and diluted with the light polyester to obtain a polyester with an inorganic nanoparticle content of 4.5wt%, and then the polyester was used for the filter pressure test. Under a certain discharge volume, the polyester was melted and passed through the filter screen with a pore size of 5μm. The filter pressure test temperature was 290℃. The total discharge volume of the polyester was 300g. The pressure before the filter screen 30min after the start of feeding was recorded as the initial pressure Pa3, and the final pressure at the end of the filter pressure test was recorded as Pa4. At this time, the filter pressure rise value P2=Pa4-Pa3. The smaller P2 is, the better the dispersion of the polyester masterbatch can be maintained during use.

[0037] (4) Characterization of inorganic nanoparticle types The polyester masterbatch chips obtained by granulation were dissolved in hexafluoroisopropanol. 1g of polyester was dissolved in 20g of hexafluoroisopropanol. Then, the chips were centrifuged to obtain inorganic nanoparticle samples. After the samples were ground into fine powders, After drying in an oven at 120°C for 12 hours, the samples were tested in an X-ray diffractometer. The radiation source was a Cu target, the wavelength of the ray was 1.54Å, the voltage was 40kV, the current was 200mA, and the test range was 5° to 60°. The relationship between the lattice spacing d and the relative intensity I / I1 of the powder was obtained. By comparing it with standard PDF (Power Diffraction files), the type of inorganic nanoparticles can be determined.

[0038] (5) Determination of inorganic nanoparticle content After knowing the type of inorganic nanoparticles (at least one of titanium dioxide, silicon dioxide, zirconium oxide, zinc oxide, and barium sulfate), take about 4 g of the polyester masterbatch, melt the sample at 360°C, flatten the sample surface with a hydraulic press, and measure the content of metal or non-metal elements with an X-ray fluorescence spectrometer (manufacturer: Rigaku, model: ZSX PrimusⅢ+), and then calculate the content of inorganic nanoparticles in the polyester masterbatch by the molecular formula.

[0039] (6) Measurement of the particle size of inorganic nanoparticles The polyester masterbatch slices obtained by granulation are dissolved in hexafluoroisopropanol. 1g of polyester is dissolved in 20g of hexafluoroisopropanol, and then centrifuged to obtain inorganic nanoparticle powder. The powder is ultrasonically washed with hexafluoroisopropanol, and this step is repeated 3 times. The picture of the inorganic nanoparticle powder is taken by SEM. After printing, 10 particles are selected and the diameter passing through the center of the particle is measured respectively. The final result is the average of 10 groups of data. These 10 groups of data are subjected to variance processing to obtain the variance value.

[0040] (7) Confirmation of the crystal form of titanium dioxide (TiO2) The polyester masterbatch slices obtained by granulation are tested for the crystallization peak position of the sample using an X-ray diffraction device, and the crystallization peak position of the common rutile titanium dioxide is also tested. The crystal form of titanium dioxide is determined by comparing the crystallization peak positions obtained by the two.

[0041] (8) Melt viscosity The polyester masterbatch chips obtained by granulation were dissolved in hexafluoroisopropanol. 1g of polyester was dissolved in 20g of hexafluoroisopropanol, and then centrifuged to obtain the upper polymer hexafluoroisopropanol solution. After the hexafluoroisopropanol was completely evaporated, a polymer solid sample was obtained. 0.4g of the polymer solid sample was weighed and dried in an oven at 150℃ for 12h. The dynamic viscoelasticity equipment E4000 made by UBM Polymer Co., Ltd. of Japan was used to test the -1 Melt viscosity at shear rate.

[0042] (9) Hue This experiment uses the SC-T spectrophotometer of Japan SUGA Company, and sets the parameters: D65 light source, 10° viewing angle, 0° illumination / 45° measurement light path geometry, and uses a 3cm observation hole to observe the slice hue. The precision of the color value is in accordance with the national standard GB / T 14190-2017 method, with the repeatability difference of L value ≤2.0, the repeatability difference of a value ≤0.4, and the repeatability difference of b value ≤0.6.

[0043] The advantages of the present invention will be described in detail below by referring to the following embodiments and comparative examples. The present invention is not limited to the following embodiments and comparative examples.

[0044] Embodiment 01:

[0045] At 235°C, 106 parts by weight of dimethyl terephthalate and 83 parts by weight of ethylene glycol (EG) were subjected to transesterification reaction in the presence of transesterification catalyst cobalt acetate (equivalent to 300ppm of polyester masterbatch mass), and calcium acetate, a dispersant equivalent to 65ppm of polyester mass in terms of alkaline earth metal, and antimony trioxide, a polycondensation catalyst equivalent to 400ppm of polyester mass, were added during the transesterification process. The esterification reaction was judged to be over after the amount of methanol reached the theoretical amount. Then, titanium dioxide ethylene glycol dispersion was added thereto twice, wherein the average particle size of titanium dioxide was 101nm, the mass of titanium dioxide added was 15wt% relative to the mass of polyester masterbatch, the first addition rate was to add titanium dioxide ethylene glycol dispersion equivalent to 0.25wt% of polyester masterbatch mass per minute, the addition time was 20min, and the second addition rate was to add titanium dioxide ethylene glycol dispersion equivalent to 0.29wt% of polyester masterbatch mass per minute, the addition time was 34min. The time interval from the end of the first addition to the start of the second addition was 20min. After the first addition of titanium dioxide ethylene glycol dispersion, ethylene glycol is heated and distilled until the molar ratio of ethylene glycol to dimethyl terephthalate in the esterification kettle is 2.46. After the second addition of titanium dioxide ethylene glycol dispersion, ethylene glycol is heated and distilled until the molar ratio of ethylene glycol to dimethyl terephthalate in the esterification kettle is 3.20. The esterification reaction product obtained above is transferred into the polymerization reaction tank through the material transfer pipe connecting the esterification reaction tank and the polymerization reaction tank. Stir for 5 minutes, add trimethyl phosphate, a heat stabilizer equivalent to 430ppm of polyester mass, and after a period of reaction, the polymer reaches the discharge current of the target viscosity, that is, the polycondensation reaction is completed, and the polymer is discharged to obtain polyester masterbatch.

[0046] The obtained polyester masterbatch was subjected to inorganic nanoparticle size statistics, terminal carboxyl content determination, and filter pressure test. The test results are shown in Table 1.

[0047] Embodiment 02~04: By changing the addition speed of the titanium dioxide ethylene glycol dispersion twice, the total addition amount of titanium dioxide is equivalent to 30wt%, 45wt% and 60wt% of the weight of the polyester masterbatch respectively. Other details are the same as in Example 01. Specific data are shown in Table 1.

[0048] Embodiment 05:

[0049] The viscosity of the polymer when it is discharged is adjusted to control the terminal carboxyl content of the polyester masterbatch. Other details are the same as in Example 01. Specific data are shown in Table 1.

[0050] Embodiment 06:

[0051] The viscosity of the polymer when it is discharged is adjusted to control the terminal carboxyl content of the polyester masterbatch. Other details are the same as those in Example 03. Specific data are shown in Table 1.

[0052] Embodiment 07:

[0053] The viscosity of the polymer when it is discharged is adjusted to control the terminal carboxyl content of the polyester masterbatch. Other details are the same as those in Example 04. See Table 1 for specific data.

[0054] Embodiment 08:

[0055] The addition amount of the dispersant calcium acetate was changed to be equivalent to 32.5 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The rest was the same as in Example 05. The specific data are shown in Table 1.

[0056] Embodiment 09:

[0057] The addition amount of the dispersant calcium acetate was changed to be equivalent to 97.5 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The rest was the same as Example 06. The specific data are shown in Table 1.

[0058] Embodiment 10:

[0059] The addition amount of the dispersant calcium acetate was changed to be equivalent to 130 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The rest was the same as Example 07. The specific data are shown in Table 1.

[0060] Embodiment 11:

[0061] The addition amount of the dispersant calcium acetate was changed to be equivalent to 15 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The rest was the same as in Example 02. The specific data are shown in Table 1.

[0062] Embodiment 12:

[0063] The addition amount of the dispersant calcium acetate was changed to be equivalent to 130 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The rest was the same as Example 05. The specific data are shown in Table 1.

[0064] Embodiments 13 to 15: The time interval from the end of the first addition to the start of the second addition of the titanium dioxide ethylene glycol dispersion was changed, and the rest was the same as Example 02. The specific data are shown in Table 2.

[0065] Embodiments 16-17: The addition rate of the titanium dioxide ethylene glycol dispersion was changed, and the rest was the same as in Example 02. The specific data are shown in Table 2.

[0066] Embodiments 18 to 21: The type of inorganic nanoparticles was changed, and the rest was the same as Example 02. The specific data are shown in Table 2.

[0067] Embodiment 22~23: The type of the alkaline earth metal acid salt compound of the dispersant was changed, and the rest was the same as Example 02. The specific data are shown in Table 2.

[0068] Embodiment 24:

[0069] When adding the titanium dioxide ethylene glycol solution, only one addition is made, and the rest is the same as in Example 02. The specific data are shown in Table 2.

[0070] Comparative Example 01: By adjusting the addition rate of the titanium dioxide ethylene glycol solution, the titanium dioxide content in the final polyester masterbatch is 70wt%. The rest is the same as Example 01. The specific data are shown in Table 3.

[0071] Due to the excessive content of titanium dioxide, the titanium dioxide in the polyester masterbatch is unevenly dispersed, resulting in agglomeration, a larger average particle size, and a high filtration pressure of the polyester masterbatch.

[0072] Comparative Example 02: The addition amount of the dispersant calcium acetate was changed to be equivalent to 5 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The rest was the same as Example 05. The specific data are shown in Table 3.

[0073] Since the addition amount of the alkaline earth metal acid salt compound (calcium acetate) is too low, the agglomeration of the inorganic nanoparticles cannot be effectively inhibited, the average particle size of titanium dioxide in the obtained polyester masterbatch is too large, and the filtration pressure of the polyester masterbatch is high.

[0074] Comparative Example 03: The addition amount of the dispersant calcium acetate was changed to be equivalent to 150 ppm of the polyester masterbatch in terms of alkaline earth metal elements. The rest was the same as Example 05. The specific data are shown in Table 3.

[0075] Since the addition amount of alkaline earth metal acid salt compound (calcium acetate) is too high, the excess alkaline earth metal particles destroy the double electrical layer of the titanium dioxide particles, resulting in particle agglomeration. The average particle size of titanium dioxide in the obtained polyester masterbatch is too large, and the filtration pressure of the polyester masterbatch is high.

[0076] Comparative Example 04: The addition rate of the titanium dioxide ethylene glycol dispersion was changed, and the rest was the same as in Example 02. The specific data are shown in Table 3.

[0077] Since the addition speed of inorganic nanoparticles is too slow, the addition time is long under the same total amount of addition, the thermal history time of the transesterification reaction is prolonged, resulting in a deterioration in the color tone of the final polyester masterbatch.

[0078] Comparative Example 05: The addition rate of the titanium dioxide ethylene glycol dispersion was changed, and the rest was the same as in Example 02. The specific data are shown in Table 3.

[0079] Since the inorganic nanoparticles are added too quickly, the added inorganic nanoparticles are not dispersed in time, and a large amount of accumulation leads to agglomeration of the inorganic nanoparticles, which cannot play the role of secondary addition. The average particle size of titanium dioxide in the obtained polyester masterbatch is too large, and the filtration pressure of the polyester masterbatch is high.

[0080]

[0081]

[0082]

Claims

1. High concentration inorganic nanoparticle polyester masterbatch, mainly composed of polyester and inorganic nanoparticles, is characterized by: The content of the inorganic nanoparticles is 15-60wt%; the polyester masterbatch contains 15-130ppm of alkaline earth metal elements; and the molar ratio of the alkaline earth metal elements to the polyester terminal carboxyl group is 0.008-0.070:

1.

2. The high-concentration inorganic nanoparticle polyester masterbatch according to claim 1, characterized in that: The molar ratio of the inorganic nanoparticles to the alkaline earth metal element is 600-4000:

1.

3. The high-concentration inorganic particle polyester masterbatch according to claim 1 or 2, characterized in that: The inorganic nanoparticles are at least one of titanium dioxide, silicon dioxide, zirconium oxide, zinc oxide and barium sulfate.

4. The high-concentration inorganic nanoparticle polyester masterbatch according to claim 1 or 2, characterized in that: The average particle size of the inorganic nanoparticles is less than 1000 nm, and the variance value of the particle size of the inorganic nanoparticles is less than 500.

5. The high-concentration inorganic nanoparticle polyester masterbatch according to claim 1 or 2, characterized in that: The alkaline earth metal element is calcium ion and / or magnesium ion.

6. The high-concentration inorganic nanoparticle polyester masterbatch according to claim 1 or 2, characterized in that: The polyester masterbatch is heated at a temperature of 290°C and a shear rate of 121.6s -1 The melt viscosity is below 2500 Pa·s.

7. The method for preparing the high-concentration inorganic nanoparticle polyester masterbatch according to claim 1 mainly comprises subjecting terephthalic acid or its esterified derivative and diol to transesterification or esterification reaction under the action of a catalyst, and then to polycondensation reaction, wherein: During the ester exchange or esterification reaction, an alkaline earth metal acid salt compound equivalent to 15 to 130 ppm of the polyester masterbatch is added in terms of alkaline earth metal elements; before the start of the polycondensation reaction, inorganic nanoparticles equivalent to 15 to 60 wt% of the polyester masterbatch are added at a rate of 0.10 to 1.20 wt% / min.

8. The method for preparing high-concentration inorganic nanoparticle polyester masterbatch according to claim 7, characterized in that: The inorganic nanoparticles are added in two times, and the interval between the end of the first addition and the start of the second addition is 20 to 60 minutes.

9. The method for preparing high-concentration inorganic nanoparticle polyester masterbatch according to claim 7, characterized in that: The acid ions in the alkaline earth metal acid salt compound are selected from at least one of acetate, butyrate and hydrochloride, and the alkaline earth metal ions are calcium and / or magnesium.

Citation Information

Patent Citations

  • Polyester composition

    JP1991287655A

  • Polyester resin and method for producing the same

    JP2002356547A

  • Polyester composition

    JP2006265376A